Synergistic effect of bodyweight resistance exercise and protein supplementation on skeletal muscle in sarcopenic or dynapenic older adults. Issue 5 (13th March 2019) - Yamada, Minoru; Kimura, Yosuke; Ishiyama, Daisuke; Nishio, Naohito; Otobe, Yuhei; Tanaka, Tomoya; Ohji, Shunsuke; Koyama, Shingo; Sato, Atsushi; Suzuki, Mizue; Ogawa, Hideyuki; Ichikawa, Takeo; et al.
Abstract : Aim: The objective of this trial was to investigate the synergistic effects of bodyweight resistance exercise and a protein supplement with vitamin D on skeletal muscle in sarcopenic or dynapenic older adults. Methods: This was a four‐arm randomized controlled trial. Sarcopenic or dynapenic older adults were recruited for this trial. After screening, a total of 112 older adults were randomly allocated among four groups; 28 older adults each were enrolled in the combined resistance exercise and nutritional supplementation group, the exercise alone group, the nutritional supplementation alone group, and the control group. Participants in the combined group and exercise alone groups took part in a bodyweight resistance exercise program for 12 weeks. Protein and vitamin D supplements were provided every day for 12 weeks for the participants in the combined group and nutritional supplementation alone groups. We assessed the echo intensity of participants' thigh muscle using ultrasonography, measured their appendicular muscle mass using a bioelectrical impedance data acquisition system, and tested their knee extension strength and physical function. Results: Participants in the combined group had a significantly greater improvement in rectus femoris echo intensity and knee extension torque than those in the other groups ( P < 0.05). Furthermore, the combined program increased appendicular muscle mass in sarcopenic older adults ( P < 0.05), but not in older adults with low physical function with normal muscle mass. Conclusions: The present study confirmed the synergistic effect of bodyweight resistance exercise and protein supplement with vitamin D on muscle quality and muscle strength in sarcopenic or dynapenic older adults.Geriatr Gerontol Int 2019; 19: 429–437 .